MONITORING ACCORDING TO ESG PRINCIPLES AND ITS IMPACT ON THE COMPETITIVENESS OF BUSINESS ENTITIES - LIVOSHKO, Tetiana (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article defines that in recent years, the realization that certain corporate risks, such as environmental, social practices and corporate governance, can significantly affect the value of the enterprise, its competitiveness and development strategy in the long run. Today, the world is united to solve global problems of the present, which can be solved through the introduction of the latest technologies and a progressive approach to business assessment. The authors emphasize the importance of ESG-investing in the process of transformation into a low carbon economy and its impact on the competitiveness of enterprises. Arsenal of effective measures for the formation of a regulatory environment has been identified. ESG-Investment, the introduction of which in domestic practice will allow to make effective and optimal management decisions. The article substantiates that the practice of external independent evaluation of ESG-face based on open sources is becoming more and more popular in Ukraine. Changing the values ​​of human life in recent years and the Covid-19 pandemic showed the need for a strategic approach to environmental and social risks. It is determined that investors are increasingly insisting on companies with ESG criteria companies, international politicians and procedures. It is substantiated that ESG strategy is a very important tool for sustainable development that allows the enterprises of the DTEK group at the highest level to integrate environmental, social and management standards. The article proves that during the restoration of the country after Russia’s aggression, almost all investments will come to Ukraine on the basis of ESG, so the drivers of sustainable development increase. Therefore, Ukrainian companies today, in these difficult times, need help in understanding and implementing these principles.